L’horizon matière de l’habiter - Julie Cattant (Projets de Paysage)
The doctoral research here submitted addresses landscape through one of its emblematic elements: the horizon. If landscape unites representation, experience and invention, as for the horizon, it is considered from the perspective of its relationships with architecture and urban space. The hypothesis is that the horizon involves dwelling and interrogates the concord between man, architecture, landscape and society. It’s at the outskirts, where the horizon is often ignored, that this study finds its political and ethical realities. From the analysis of the “La Duchère” neighborhood in Lyon to the study of architects especially interested in the horizon, this research insists on the necessity of relationships between architecture and its environment. It also interrogates the concord between architecture and mankind that some architects name harmony, measure, meeting or correctness.